Effects of Lumbopelvic Neutralization on the Electromyographic Activity, Lumbopelvic and Knee Motion during Seated Knee Extension in Subjects with Hamstring Shortness - Jeon, Hye-Seon; Kim, Su-Jung; Lee, Won-Hwee; Ha, Sung-Min; Yi, Chung-Hwi; Kwon, Oh-Yun; Park, Kyue-Nam (Journal of Physical Therapy Science, 2012)
[Purpose] The purpose of this study was to examine the effects of lumbopelvic neutralization on the angle of knee extension, lumbopelvic motion, and the electromyographic (EMG) activities of the quadriceps, hamstrings, and rectus abdominis muscles of subjects with hamstring shortness during seated knee extension. [Subjects] Twenty young subjects (14 men, 6 women) with hamstring shortness were recruited for this study. [Methods] A pressure biofeedback unit was used to monitor the lumbopelvic neutralization during seated knee extension with lumbopelvic neutralization. The EMG activity and kinematic data were measured during seated knee extension with and without lumbopelvic neutralization. Surface EMG was used for measuring the muscle activities of the quadriceps, hamstrings, and rectus abdominis muscles. The angles of knee extension, lumbar flexion, lumbar rotation, and posterior pelvic tilt were measured using a 3-dimensional motion analysis system. [Results] The angles of the lumbar flexion, lumbar rotation, posterior pelvic tilt, and knee extension decreased significantly when performing seated knee extension with lumbopelvic neutralization compared to performing the same maneuver without lumbopelvic neutralization. The EMG activities of the medial and lateral hamstrings, quadriceps, and rectus abdominis decreased significantly during seated knee extension with lumbopelvic neutralization using a pressure biofeedback unit. [Conclusion] Seated knee extension exercise with lumbopelvic neutralization may be useful for minimizing compensatory lumbopelvic motion and preventing compensatory hamstrings and rectus abdominis muscle activities of subjects with hamstring shortness during seated knee extension.